Evaluating mineral revenue transparency in Eswatini against the extractive industries transparency initiative - Gerber, Leonardus J. (University of Pretoria, 2022)
Mini Dissertation (LLM (Extractive Industry Law in Africa))--University of Pretoria, 2022.